Spatiotemporal evolution and trend prediction of coupled coordination between digital technology and manufacturing green transformation from provinces in China - Huang, Xin; Deng, Hongbing (Frontiers in Environmental Science, 2025)
China is actively promoting the deep integration of digital technology and manufacturing and helping the manufacturing industry develop into high‐end, intelligent, and green. As the concept of green development gradually deepens and the international situation becomes increasingly severe, it is necessary to discuss the coordinated development of digital technology and the manufacturing green transformation (MGT), which will better promote the realization of the goals of “double carbon,” “digital power” and “manufacturing power.” Based on this, this paper adopts the coupling coordination model, kernel density estimation, Dagum Gini coefficient decomposition, and spatial autocorrelation to conduct a spatiotemporal evolution analysis of the coupling coordination degree (the D‐G system) of digital technology and MGT in 30 provinces (municipalities, autonomous regions) of mainland China from 2011 to 2020, and adopting the spatial Markov chain to predict its evolutionary trend. The key findings of the study are as follows: (1) Digital technology and MGT have been progressing steadily in China, with continuous improvements in the level of development; (2) The degree of coupling coordination has shown consistent growth over the years, yet the distribution remains relatively uneven, exhibiting a “trapezoidal” spatial pattern with higher values in the eastern regions and lower values in the western regions; (3) Regional differences play a crucial role in the overall differences of the D-G system; and (4) The traditional Markov chain results show that the probability of the D‐G system maintaining the original state stage in the future is greater than 88.67%. The spatial Markov chain results show that the state type of the neighborhood background affects the state transition of the coupling coordination degree. The coupling coordination development of each province will not only be subjected to the “spatial drag” of the neighboring region but also show the phenomenon of “club convergence.“ These findings provide valuable theoretical insights and practical recommendations for fostering the simultaneous advancement of digital development and sustainable development.